Malaysian royal commissions: an evaluation on the effectiveness in solving issues of public interest / Adida Izani Ishak ...[et al.] - Ishak, Adida Izani; Morad, Mahanum; Juhaidi Yean, Nur Atasha Syakina; William, Thressa (2009)
This legal research was conducted with the aim of finding out the effectiveness and functions of established Royal Commissions, and giving out suggestions on how to improve future Royal Commissions. Specific legislation has been enacted to govern the establishments of these Commissions. However, there is no transparency in their work, not to mention the fact that the Enquiry Act 1950 has certain lacunas that doesn't fully cover all the necessary matters in this regard. This is why some people question the functions and effectiveness of these Commissions. Thus, the commencement of this research begins. The scope of this legal research is on the functions and effectiveness of established Royal Commissions. In addition, a comparative analysis was made against commissions established in India and the United Kingdom. This legal research is based on the qualitative method i.e. library-based study, due to the time constraints. Legislations, cases, reports and other necessary sources that relates to Royal Commissions are also used. It is hoped that this legal research will provide some understanding as to the functions and effectiveness of Royal Commissions and proposed suggestions and recommendations on how to improve future Commissions.